2020
DOI: 10.1017/s0007485320000504
|View full text |Cite
|
Sign up to set email alerts
|

Repellent activity of Tanacetum parthenium (L.) and Tanacetum vulgare (L.) essential oils against Leptinotarsa decemlineata (Say)

Abstract: The Colorado potato beetle, Leptinotarsa decemlineata (Say), is one of the most destructive pest species to have developed resistance to most chemical insecticides. We determined the composition and evaluated the potential of Tanacetum parthenium L. and Tanacetum vulgare L. (Asteraceae family) essential oil (EO) application as an alternative eco-friendly control strategy against L. decemlineata. We assessed the antifeedant activity for L. decemlineata larvae and adults by estimating the damage to potato leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Lazarević et al reported that at higher EO concentrations, both third instar larvae and adult T. parthenium and T. vulgare required less time to choose an untreated leaf disc. Additionally, EO provoked rapid movement away from the treated leaf disc especially at the highest concentration [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lazarević et al reported that at higher EO concentrations, both third instar larvae and adult T. parthenium and T. vulgare required less time to choose an untreated leaf disc. Additionally, EO provoked rapid movement away from the treated leaf disc especially at the highest concentration [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to different studies, T. parthenium extracts exhibit anti-nociceptive [13][14][15], antioxidant [13,[16][17][18][19][20][21], antibacterial [22], insecticidal [23], anti-inflammatory, neuromodulatory, antispasmodic, and uterine stimulant activity [24,25]. Investigations on feverfew EO have indicated antimicrobial [26][27][28][29][30][31], antioxidant [32], repellent [33], cytotoxic, and low anti-inflammatory [34] properties. Parthenolide, a sesquiterpene lactone isolated from the plant, has been reported to demonstrate antiinflammatory [35][36][37][38][39][40][41][42][43][44][45], neuroprotective [46,47], cholesterol-lowering [48], antiviral [49], antileishmanial [50], and antitumor [51][52][53][54][55][56][57] effects.…”
Section: Introductionmentioning
confidence: 99%